Francuscy i polscy jeńcy wojenni. Braterstwo doświadczeń i świadectwa - Panné, Jean-Louis; Paprocka-Piotrowska, Urszula (Pamięć i Sprawiedliwość, 2005)
In 1940, a significant number of French prisoners got in touch with Polish soldiers, themselves prisoners, or with Polish civilians with whom they mixed in the “kommandos” to which score of them were dispersed. Those forced encounters influenced the way the two nationalities perceived each other, and the spiritual brotherhood, born under arms, lasted after the defeat. With the advance of the Soviet army, French and Polish prisoners hadshared common experience. If the stories of the ex-POWs returning to France were ignored, contained or scorned owing to the political and social strength of the French Communist Party, the fact remains, nevertheless, that this moment of shared history Polish and French provided a basis for the profound sympathy that links the two nations.